Variscan Metamorphism - Ribeiro, M.L. (2020)
Various segments of Variscan crust are currently exposed in Iberia in response to successive tectonic events during the Variscan orogeny itself and subsequent extensional and compressive events during the Alpine cycle, all accompanied by surface erosion, and collectively contributing to their exhumation. We review the main characteristics and geodynamic contexts of the metamorphic complexes developed in Iberia during the Variscan cycle, which include: (i) LP-HT complexes associated to the Cambrian-Early Ordovician rift stage; (ii) HP-LT complexes associated to subduction; and (iii) syn-to-post-collisional, MP and LP/HT complexes from the hinterland to the foreland fold-and thrust belts. All the above contexts are illustrated with case studies. Finally, a review of Variscan metamorphism in the Pyrenees and Catalan Coastal Ranges, located far away from the Rheic suture is also presented.